2018
DOI: 10.1016/j.foodchem.2018.06.099
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic effervescent tablets containing ionic liquids as a non-conventional extraction and dispersive agent for determination of pyrethroids in milk

Abstract: Conventional magnetic effervescent tablet has many drawbacks, such as not practicable for field processing, rapid moisture absorption, and poor tablet storage characteristics. Herein, we developed a novel magnetic effervescent tablet containing ionic liquid microextraction (MET-ILM) for determination of pyrethroids in dairy milk. It contains only NaCO as an alkali source (no acidic source) in the FeO magnetic tablet; the CO-forming reaction is initiated in the acidic solution containing the analytes, and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The extraction recoveries (Figure ) for the target analytes increased with increasing addition of sodium chloride and then decreased, which indicated that a small amount of sodium chloride played an active role. This could be explained by considerations of salting‐out effects and salting‐in effects . Salting‐out enhances the transfer of analytes into organic extraction solvent and therefore increases the amount extracted, however, salting‐in could lead to the dissolution of the analytes in water thus decreasing the amount extracted and reducing the extraction efficiency .…”
Section: Resultsmentioning
confidence: 99%
“…The extraction recoveries (Figure ) for the target analytes increased with increasing addition of sodium chloride and then decreased, which indicated that a small amount of sodium chloride played an active role. This could be explained by considerations of salting‐out effects and salting‐in effects . Salting‐out enhances the transfer of analytes into organic extraction solvent and therefore increases the amount extracted, however, salting‐in could lead to the dissolution of the analytes in water thus decreasing the amount extracted and reducing the extraction efficiency .…”
Section: Resultsmentioning
confidence: 99%
“…This transformation reaction can be done by adding the metathesis reagent after the tablet dissolution [65] or using it as a tablet ingredient [66]. In other cases, the H-donor is added directly to the sample [67], or the IL plays a double role as extractant and H-donor [68]. Wang et al have recently proposed magnetic ILs as extractants, which simplifies the overall process as the MNPs are no longer necessary [69].…”
Section: Solventsmentioning
confidence: 99%
“…On the other hand, the rapid moisture absorption by ETs could also lead to destabilizing the drug preparations and therefore reducing the pharmacodynamic efficacy. 30,31 Therefore, it is also benecial to reduce this undesirable property of ETs.…”
Section: Tablet Hygroscopicitymentioning
confidence: 99%